Mounting and Sustaining the Violence Against Women Research and Evaluation Program at the National Institute of Justice. (June 2013) - Auchter, Bernard; Moore, Angela
The Violence Against Women Act of 1994 (VAWA) mandated a number of research efforts that stimulated a dramatic enhancement to violence against women research supported by the National Institute of Justice (NIJ). This article documents and provides a perspective on key components in the history, development, and accomplishments of the Violence Against Women (VAW) research and evaluation program of NIJ. The article is comprised of four key parts: (a) progress of the research program and how leadership, planning, and collaboration were the catalysts in instituting the program; (b) significant research issues confronted and managed, including measurement, evaluation rigor, and gender symmetry; (c) critical conflicts in the field, such as calls for greater attention to sexual assault and violence against minorities as well as resistance to research on perpetrators and male victims; and (d) possible research directions for the future and a concluding comment.